Clinical Application of Whole Genome Array Improves the Diagnosis of Pediatric Brain Tumors. (December 2017) - Shao, Lina; Miller, Sue; Koschmann, Carl; Camelo-Piragua, Sandra
Pediatric brain tumors are the leading cause of childhood cancer mortality. Recurring genetic abnormalities play an essential role in the diagnosis and prognosis of pediatric brain tumors. However, clinical workup has not routinely included whole genome assessment. Here, we present high resolution whole genome array results in 11 pediatric brain tumors. Array identified clinically relevant abnormalities in all samples. Copy number aberrations with targeted therapy implication, GOPC-ROS1 fusion, CDK4 amplification, and NF1 deletion, were detected in 3 cases. In addition, array detected recurring genetic abnormalities, including KIAA1549-BRAF fusion, 19q13.42 amplification, i(17q), and monosomy 6, which assisted accurate histological diagnosis in pediatric brain tumors. In conclusion, our results show that whole genome high-resolution array detects diagnostic and treatment-relevant copy number abnormalities in pediatric brain tumors.